2011
DOI: 10.1007/s11764-011-0180-z
|View full text |Cite
|
Sign up to set email alerts
|

Adult cancer survivorship care: experiences from the LIVESTRONG centers of excellence network

Abstract: Background The objectives of this study were to characterize survivorship models of care across eight LIVESTRONG Survivorship Center of Excellence (COE) Network sites and to identify barriers and facilitators influencing survivorship care. Methods Using the framework of the Chronic Care Model (CCM), quantitative and qualitative methods of inquiry were conducted with the COEs. Methods included document reviews, key informant telephone interviews with 39 participants, online Assessment of Chronic Illness Care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 15 publications
4
49
0
Order By: Relevance
“…We are therefore highlighting the urgent need for appropriate studies targeting secondary prevention of cancer for bca survivors, especially studies that explore lifestyle and behavioural factors, including diet. Campbell et al 84 indicated that support for patient self-management and use of evidence-based health promotion interventions were areas of relative weakness when survivorship models of care were analyzed in 8 livestrong Survivorship Centers of Excellence Network sites in the United States, corroborating our statement.…”
Section: Discussionsupporting
confidence: 82%
“…We are therefore highlighting the urgent need for appropriate studies targeting secondary prevention of cancer for bca survivors, especially studies that explore lifestyle and behavioural factors, including diet. Campbell et al 84 indicated that support for patient self-management and use of evidence-based health promotion interventions were areas of relative weakness when survivorship models of care were analyzed in 8 livestrong Survivorship Centers of Excellence Network sites in the United States, corroborating our statement.…”
Section: Discussionsupporting
confidence: 82%
“…We are therefore highlighting the urgent need for reliable studies that target secondary prevention of cancer for crc survivors, especially those that explore lifestyle and behavioural factors, including diet. Campbell et al 18 mention that support for patient self-management and use of evidence-based health-promotion interventions were areas of relative weakness when analyzing survivorship models of care used at 8 livestrong Survivorship Centers of Excellence Network sites in the United States, corroborating our statement.…”
Section: Alcoholsupporting
confidence: 80%
“…Although scps are apparently beneficial, there are pragmatic challenges in implementing them not only in crc, but also across all disease groups. Examples include choosing a format, finding resources, managing time constraints, and allocating personnel 18 .…”
Section: Introductionmentioning
confidence: 99%
“…With permission, interviews were audio-taped and transcribed verbatim. An openended interview script utilized the framework of the CCM [4,14] and added questions about the strengths and weaknesses of the COE, challenges ORIGINAL RESEARCH (lessons learned) for program development, important accomplishments of the COE, changes over time, and the value of survivorship care to oncology practice. Site visits were conducted in May 2009 with three of the earliest-funded COEs.…”
Section: Data Collectionmentioning
confidence: 99%
“…Using both quantitative and qualitative data, findings from the study offered support for several domains of the chronic care model (CCM) which emphasizes the importance of six elements essential to improve chronic illness care: health system organization, delivery design, clinical information systems, selfmanagement care, decisional support, and community linkages [4]. A major issue that emerged from the qualitative data was the experience of the COEs in adopting and implementing the survivorship care programs into the oncology practices of their institutions.…”
mentioning
confidence: 97%